Introduction to the Special Issue: A Case for School Counseling Leadership. Issue 1 (2017) - Young, Anita A.; Dollarhide, Colette T.
In this introduction article to the special issue of Professional School Counseling on "School Counseling Leadership in Practice, " the guest editors advance the next evolution of school counseling leadership by presenting a compilation of research, conceptual, and practitioner articles. The special issue emphasizes how school counselors can lead efforts endorsed by the American School Counselor Association Mindsets & Behaviors, examines ways social justice leadership is manifested in school counseling programs, and explores new leadership paradigms.